2010
DOI: 10.1143/jjap.49.02ba02
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Combinatorial Method Aiding Research on Single-Walled Carbon Nanotube Growth on Substrates

Abstract: Establishing fabrication methods of carbon nanotubes (CNTs) is essential to realize many applications expected for CNTs. Catalytic growth of CNTs on substrates by chemical vapor deposition (CVD) is promising for direct fabrication of CNT devices, and catalyst nanoparticles play a crucial role in such growth. We have developed a simple method called ''combinatorial masked deposition (CMD)'', in which catalyst particles of a given series of sizes and compositions are formed on a single substrate by annealing gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…catalysts presenting a gradient of iron thickness, Hasegawa et al [319] evidenced that millimetre-tall VACNT forests can be grown without addition of water if the carbon precursor supply is set below a certain limit in order to retain an active catalyst; water only extends the catalyst lifetime when an excess precursor supply is used. They also found water addition to widen the window of catalyst thickness for VACNT growth toward higher thicknesses and to suppress nanotube growth from the smallest catalyst particles [299].…”
Section: Proportion Of Catalyst Particles Active For Nanotube Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…catalysts presenting a gradient of iron thickness, Hasegawa et al [319] evidenced that millimetre-tall VACNT forests can be grown without addition of water if the carbon precursor supply is set below a certain limit in order to retain an active catalyst; water only extends the catalyst lifetime when an excess precursor supply is used. They also found water addition to widen the window of catalyst thickness for VACNT growth toward higher thicknesses and to suppress nanotube growth from the smallest catalyst particles [299].…”
Section: Proportion Of Catalyst Particles Active For Nanotube Growthmentioning
confidence: 97%
“…notably reported that the addition of water to ethylene degrades the quality of CCVD-grown SWCNTs [299]. Similarly, Gao et al [279] found that using an oxygen-containing precursor such as ethanol yielded a higher linear density of defects than using methane.…”
Section: Defect Density and Carbonaceous Impuritiesmentioning
confidence: 97%
“…However, these systems present problems related to the preparation of long term stable coatings [9][10]. Frequently, the deposition of the catalytic layer over the surface of metallic substrate is carried out by means of a washcoating stage, requiring this step a cautious attention, especially in the case of complex geometries, like of that of foams or cloths [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…1 For electronics, even presently high price of the CNT (∼1k $/g) is not considered as an obstacle. 2 What still remains a challenge is the practical control of the single-walled CNT symmetry type, the chirality (n, m).…”
Section: Introductionmentioning
confidence: 99%